The role of philosophy in the formation of the ancient Turkic state policy of Kazakhstan as an independent sovereign state. - Kalybayeva., К. S. (Journal of Oriental Studies, 2016)
This article discusses current research problems and the formation of the ancient Turkic statehood analizirutsya its role in the formation of the Kazakh independent statehood.